2013
DOI: 10.5897/jmpr12.1211
|View full text |Cite
|
Sign up to set email alerts
|

Ethnobotanical study of medicinal plants of the Ipassa-Makokou Biosphere Reserve, Gabon: Plants used for treating malaria

Abstract: Malaria remains a major cause of illness and death as well as a contributing factor to poverty in tropical and subtropical regions. Ethnobotanical surveys conducted in the periphery of the Ipassa -BiosphereReserve (Gabon) allowed to identify 61 plant species used by the Baka pygmies, Fang, Kota and Kwélé ethnic groups for the treatment of malaria. These plants are distributed in 55 genera and 34 botanical families. Leaves are among the plant parts that are largely cited (62% of citations), followed by stem bar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The Congo Basin region itself is megadiverse in plant species, including medicinal plants (Light et al, 2016). Screening studies for antimalarial medicinal plant species from Cameroon (Betti, 2002;Saotoing et al, 2011;Titanji et al, 2008;Kuete and Efferth, 2010;Betti et al, 2013a), Gabon (Betti et al, 2013b), the Central African Republic (Lakouéténé et al, 2009), Republic of Congo (Mbatchi et al, 2006;Nsonde-Ntandou et al, 2005) and Guinea Equatorial (Gomez Marín and Merino Cristóbal, 1990) have demonstrated the potential of traditional medicinal plants as source of antimalarial substances. Furthermore, the DRC, with about half of the African humid forests, ranks fifth in the world for the diversity of plant species (UNESCO, 2010;Masunda et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The Congo Basin region itself is megadiverse in plant species, including medicinal plants (Light et al, 2016). Screening studies for antimalarial medicinal plant species from Cameroon (Betti, 2002;Saotoing et al, 2011;Titanji et al, 2008;Kuete and Efferth, 2010;Betti et al, 2013a), Gabon (Betti et al, 2013b), the Central African Republic (Lakouéténé et al, 2009), Republic of Congo (Mbatchi et al, 2006;Nsonde-Ntandou et al, 2005) and Guinea Equatorial (Gomez Marín and Merino Cristóbal, 1990) have demonstrated the potential of traditional medicinal plants as source of antimalarial substances. Furthermore, the DRC, with about half of the African humid forests, ranks fifth in the world for the diversity of plant species (UNESCO, 2010;Masunda et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Persea americana is cultivated for its nutritious fruit which contains vitamins and minerals [3]. The leaf is used for the treatment of malaria [3][4][5], dysentery, coughs, liver obstructions and high blood pressure [6]. It is used to enhance menstrual flow and reduce high levels of uric acid in the body [6].…”
Section: Introductionmentioning
confidence: 99%